Applied statistics and probability for engineers - Montgomery, Douglas C. (J. Wiley, 1999)
This text brings statistical tools to engineers and scientists who design and develop new products, new manufacturing systems and processes and who improve existing systems. Written by engineers for engineers, the examples and exercises are engineering-based, containing real data. And because computers are used to apply statistical methods to solve problems, output is presented from Statgraphics and SAS to illustrate what can be done with modern statistical software. Readers will master discrete and continuous random variables and probability distributions; point and interval estimation; testing hypotheses; simple and multiple linear regression; design of experiments; nonparametric statistics; and statistical quality control.